The effect of low-dose esketamine on pain and post-partum depression after cesarean section: A prospective, randomized, double-blind clinical trial - Shen, Jiahong; Song, Congzhong; Lu, Xinlei; Wen, Yuxin; Song, Shaobo; Yu, Jing; Sun, Jianliang (Frontiers in Psychiatry, 2023)
Objective To observe and evaluate the effect of a single intravenous injection of low-dose esketamine on post-operative pain and post-partum depression (PPD) in cesarean delivery patients. Methods A total of 210 patients undergoing elective cesarean delivery under combined spinal-epidural anesthesia were divided into an esketamine group (Group S, n = 105) and a normal saline group (Group L, n = 105) by a random number table. At 5 min after childbirth, patients in the S group were given 0.25 mg/kg esketamine, whereas patients in the L group received an equal volume of saline. The primary outcomes included post-operative pain control according to the Numerical Rating Scale (NRS) and the incidence of PPD according to the Edinburgh Post-partum Depression Scale (EPDS). The secondary outcomes included analgesia-related adverse events and Ramsay sedation scores. Results This clinical study was a prospective, randomized, double-blind trial. A total of 210 patients were enrolled in this study. The NRS pain (cough pain) score was lower in the S group than in the L group at 24 h after surgery (P = 0.016), and there was no significant difference in resting pain and mobilization pain at 4, 8, and 48 h after surgery or resting pain at 24 h after surgery between the two groups. There was no significant difference in the prevalence of PPD between the two groups on the day before delivery, or at the first week, the second week, or the fourth week after childbirth. At 5 min after dosing, the incidence of hallucinations (P < 0.001) and dizziness (P < 0.001) was higher in the S group than in the L group. At 15 min after dosing, the incidence of dizziness (P < 0.001) and nausea (P = 0.011) was higher in the S group than in the L group. The incidence of dizziness (P < 0.001) was higher in the S group than in the L group when leaving the operating room. The Ramsay scores in Group S were lower than in Group L at 5 min (p < 0.001), 15 min (p < 0.001) after dosing and at the time of leaving the operating room (p < 0.001). Conclusion In this study, a single intravenous injection of 0.25 mg/kg esketamine did not reduce the incidence of depression at 1, 2, or 4 w post-partum but improved pain during exercise at 24 h post-operatively under the conditions of this clinical trial. Clinical trial registration [www.chictr.org.cn], identifier [ChiCTR2100054332].